2020
DOI: 10.1007/s00402-020-03625-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of the BoneWelding®Fiji® anchor for the treatment of Stener lesions of the thumb

Abstract: Introduction A new technology (Sportwelding®) was recently presented, which uses ultrasonic energy to meld a resorbable suture anchor at the interface with the host bone. A standardized clinical use was not investigated yet. This study prospectively evaluated the surgical and clinical outcomes of the Fiji Anchor® (Sportwelding®, Schlieren, Switzerland) in the repair of an ulnar collateral ligament lesion of the metacarpophalangeal joint of the thumb. Material and methods The range of motion, grip and pinch s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A total of 20 studies reported on postoperative metacarpophalangeal stability (Abrahamsson et al., 1990; Başar et al., 2014, 2020; Beauperthuy and Burke, 1997; Crowley et al., 2013; Delma et al., 2022; Huber et al., 1997; Kara et al., 2019; Kastenberger et al., 2021; Kozin, 1995; Lee et al., 2020; Moharram, 2013; Osterman et al., 1981; Patel et al., 2022; Rocchi et al., 2014; Saetta et al., 1992; Sollerman et al., 1991; Sourmelis, 1997; Vihtonen et al., 1993; Weiland et al., 1997). Seven studies objectively or subjectively compared stability with the unoperated thumb, five studies reported the number of patients with valgus stress testing of the thumb showing ≤20° and eight studies subjectively reported the number of patients with clinically stable MCP joints.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 studies reported on postoperative metacarpophalangeal stability (Abrahamsson et al., 1990; Başar et al., 2014, 2020; Beauperthuy and Burke, 1997; Crowley et al., 2013; Delma et al., 2022; Huber et al., 1997; Kara et al., 2019; Kastenberger et al., 2021; Kozin, 1995; Lee et al., 2020; Moharram, 2013; Osterman et al., 1981; Patel et al., 2022; Rocchi et al., 2014; Saetta et al., 1992; Sollerman et al., 1991; Sourmelis, 1997; Vihtonen et al., 1993; Weiland et al., 1997). Seven studies objectively or subjectively compared stability with the unoperated thumb, five studies reported the number of patients with valgus stress testing of the thumb showing ≤20° and eight studies subjectively reported the number of patients with clinically stable MCP joints.…”
Section: Resultsmentioning
confidence: 99%